Fostering Digital Engagement and Customer Retention in Indian Insurance : An Empirical Study - Singh, Neha; Panigrahi, Rajeshwari; Shekhar, Rashmi (Indian Journal of Marketing, 2024)
Purpose : Internet penetration in India has significantly increased over the past decade, making digital engagement accessible and affordable. This paper investigated the digital engagement of life insurance customers in India, its influence on customer retention, and the impact of perceived usefulness, perceived ease of use, and perceived value. Methodology : A mixed method approach was adopted based on an exploratory sequential design to identify the constructs and test their relationship. The authors analyzed data from 375 respondents and used confirmatory factor analysis and path analysis to test the main hypotheses using the AMOS v24 software. Findings : The findings showed that perceived ease of use and usefulness positively impacted consumers’ digital engagement. In the life insurance industry, digital engagement has a large and favorable impact on perceived value and customer retention, with perceived value acting as a partly mediating factor in customer retention. Practical Implications : Promoting the digital adoption of services among consumers is imperative for service providers to ensure better customer management, irrespective of sector and service or product. The consumer decision-making process is intricate in the life insurance sector due to the product’s complexity and the long-term association between the consumer and service provider. The study findings will help service providers focus on significant touchpoints to improve customer engagement by enhancing the engagement activities’ ease of use, usefulness, and perceived value. Originality : The paper extended our understanding of the determinants of digital engagement and its subsequent impact on consumers in the context of life insurance, which has not been explored in the existing literature.